1545. Three Site Testing for Sexually Transmitted Infections for People Living with HIV in One Southeastern Ryan White HIV/AIDS Program Clinic: First Year of Experience. (31st December 2020) - Geba, Maria; Powers, Samuel; Williams, Brooke; Dort, Kathryn R; McQuade, Elizabeth T Rogawski; McManus, Kathleen A
Abstract: Background: For comprehensive care, it is recommended that people living with HIV who are sexually active have annual multisite testing for gonorrhea and chlamydia. Appropriate testing is defined by testing at all sites of sexual exposure (urogenital, pharyngeal, rectal). In the first year of 3 site testing at our HIV clinic, we aimed to describe (1) the rate of appropriate sexually transmitted infection (STI) testing, (2) the factors associated with STI diagnosis, and (3) the percentage of extragenital STIs that would have been missed with only urogenital testing. Methods: Participants were > 14 years old with > 1 in-person medical visit at the Ryan White HIV/AIDS Program clinic in 2019. We collected demographics, reported sexual activity, and STI test dates and results. Controlling for number of sites tested, a log-binomial model was used to estimate the association of different characteristics with an STI diagnosis. Results: For this cohort (n=857; Table 1), 44% reported sexual activity, 34% reported no sexual activity and 22% had no sexual activity information recorded. Of 1185 STI tests performed for 491 participants, 51 STIs were diagnosed in 33 participants. One STI was diagnosed for a female (0.7%). Overall, 68% (253/375) received appropriate urogenital testing, 63% (85/134) received appropriate pharyngeal testing and 69% (72/105) received appropriate rectal testing. For male participants with > 1 STI test (n=347), Hispanic ethnicity was associated with an STI diagnosis (Table 2). Of those with concurrent extragenital and urogenital tests, 96% of people with an STI (n=26) were positive at only an extragenital site. Table 1: Study Participants' Characteristics Table 2: Factors Associated with Being Diagnosed With a Sexually Transmitted Infection for Men Living With HIV: Frequencies and Results of Univariable and Multivariable Log-binomial Model Conclusion: Nearly a quarter of participants had no sexual activity information recorded in the year, which is an area for improvement. Despite newly adopting 3 site testing, appropriate extragenital and urogenital testing rates were similar and were high compared with national averages. There was no obvious clinician/patient bias against extragenital testing. Hispanic male participants' higher STI diagnosis rate may point to more condomless sex in this population. Based on the identification of many infections exclusively at extragenital sites, we likely missed STIs previously. This highlights the importance of 3 site testing availability and testing at all appropriate sites. Disclosures: Kathleen A. McManus, MD, MSCR, Gilead Sciences, Inc (Research Grant or Support, Shareholder)